Does monetary policy impact international market co-movements? - Massimiliano Caporin; Loriana Pelizzon; Alberto Plazzi (Leibniz Institute for Financial Research SAFE, 2020)
We show that FED policy announcements lead to a significant increase in international comovements in the cross-section of equity and in particular sovereign CDS markets. The relaxation of unconventionary monetary policies is felt strongly by emerging markets, and by countries that are open to the trading of goods and flows, even in the presence of floating exchange rates. It also impacts closed economies whose currencies are pegged to the dollar. This evidence is consistent with recent theories of a global financial cycle and the pricing of a FED's put. In contrast, ECB announcements hardly affect comovements, even in the Eurozone.
Keywords: E58; G12; G15; 330; Unconventional Monetary policy; Quantitative easing; Mundellian trilemma; Comovements; Sovereign credit risk